Profiles of circumscribed interests in autistic youth - Spackman, Emily; Smillie, Luke D.; Frazier, Thomas W.; Hardan, Antonio Y.; Alvares, Gail A.; Whitehouse, Andrew; Uljarević, Mirko (Frontiers in Behavioral Neuroscience, 2023)
Circumscribed interests encompass a range of different interests and related behaviors that can be characterized by either a high intensity but otherwise usual topic (referred to as restricted interests [RI]) or by a focus on topics that are not salient outside of autism (referred to as unusual interests [UI]). Previous research has suggested that there is pronounced variability across individuals in terms of the endorsement of different interests, however, this variability hasn’t been quantified using formal subtyping approaches. Therefore, using Latent Profile Analysis in a sample of 1892 autistic youth (Mage = 10.82, SDage = 4.14; 420 females), this study aimed to identify subgroups based on the RU and UI profiles. Three profiles of autistic individuals were identified. They were characterized as Low CI, Predominantly RI, and Predominantly UI. Importantly, profiles differed on several key demographic and clinical variables, including age, sex composition, IQ, language level, social and communication abilities, anxiety, and obsessive-compulsive behaviors. Although replication across other samples is needed, profiles identified in this study are potentially promising for future research given their distinct profiles of RI and UI and unique patterns of associations with key cognitive and clinical variables. Therefore, this study represents an important initial step towards more individualized assessment and support for diverse presentations of CI in autistic youth.